X–Y Interactions Underlie Sperm Head Abnormality in Hybrid Male House Mice. Issue 4 (1st April 2014) - Campbell, Polly; Nachman, Michael W
Abstract: The genetic basis of hybrid male sterility in house mice is complex, highly polygenic, and strongly X linked. Previous work suggested that there might be interactions between the Mus musculus musculus X and the M. m. domesticus Y with a large negative effect on sperm head morphology in hybrid males with an F1 autosomal background. To test this, we introgressed the M. m. domesticus Y onto a M. m. musculus background and measured the change in sperm morphology, testis weight, and sperm count across early backcross generations and in 11th generation backcross males in which the opportunity for X–autosome incompatibilities is effectively eliminated. We found that abnormality in sperm morphology persists in M. m. domesticus Y introgression males, and that this phenotype is rescued by M. m. domesticus introgressions on the X chromosome. In contrast, the severe reductions in testis weight and sperm count that characterize F1 males were eliminated after one generation of backcrossing. These results indicate that X–Y incompatibilities contribute specifically to sperm morphology. In contrast, X–autosome incompatibilities contribute to low testis weight, low sperm count, and sperm morphology. Restoration of normal testis weight and sperm count in first generation backcross males suggests that a small number of complex incompatibilities between loci on the M. m. musculus X and the M. m. domesticus autosomes underlie F1 male sterility. Together, these results provide insight into the genetic architecture of F1 male sterility and help to explain genome-wide patterns of introgression across the house mouse hybrid zone.